Chronic traumatic encephalopathy in sport: a systematic review - Gardner, A.; Iverson, G. L.; McCrory, P. (British Journal of Sports Medicine, 2014)
Objective: To provide a critical review of chronic traumatic encephalopathy (CTE) by considering the range of clinical presentations, neuropathology and the strength of evidence for CTE as a distinct syndrome. Data sources: Seven electronic databases were searched using a combination of MeSH terms and key words to identify relevant articles. Review methods: Specific inclusion and exclusion criteria were used to select studies for review. Data extracted where present included study population, exposure/outcome measures, clinical data, neurological examination findings, cognitive assessment, investigation results and neuropathology results. Results: The data from 158 published case studies were reviewed. Critical differences between the older descriptions of CTE (the `classic` syndrome) and the recent descriptions (the `modern` syndrome) exist in the age of onset, natural history, clinical features, pathological findings and diagnostic criteria, which suggests that modern CTE is a different syndrome. The methodology of the current studies does not allow determination of aetiology or risk factors. Conclusions: The clinicopathological differences between the `classic` CTE syndrome and the `modern` syndrome suggest that the new syndrome needs a different nomenclature. Further research is required to clearly define the clinical phenotype of the modern CTE syndrome and establish the underlying aetiology. Future research needs to address these issues through large-scale, prospective clinicopathological studies.